A prospective interventional study to assess the advantage of premedication with sublingual nitroglycerin in evaluation of peripheral vascular disease with computed tomography peripheral angiography - B Dhanalakshmi; K P Shijith; Prafull Sharma (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2022)
Objectives: The objectives of this study were to investigate the influence of sublingual nitroglycerin (NTG) administration on peripheral vessel diameter, the number of evaluable segments, image quality, and adverse effects in patients with peripheral vascular disease (PVD) undergoing multidetector computed tomography (MDCT) angiography. Methods: A prospective randomized comparative interventional study was conducted on 48 inpatients with clinical diagnosis of PVD. The study patients were divided into two groups: one which was premedicated with 5 mg of sublingual NTG (NTG group) and the other without the use of NTG. MDCT images were recorded after 5 min of drug administration. The 10 segments of upper-limb vessels and 15 segments of lower-limb vessels were evaluated for diameter (mm), intraluminal contrast opacification (Hounsfield unit), collaterals, and stenosis (%). The data were entered in MS Excel and analyzed using SPSS. P < 0.05 was considered statistically significant. Results: The NTG group showed a statistically significant increase in diameter of radial artery (P = 0.01), common femoral artery, and all arterial segments of lower limb (P<0.05). The intraluminal contrast attenuation was higher in all segments (P < 0.05) in lower limbs. Good and continuous visualization of collateral vessels in segments with > 50% stenosis or occlusion was seen in the NTG group than the non-NTG group (P < 0.05). Conclusion: Sublingual NTG administration results in significant peripheral vessel dilatation, thus improving number of evaluable distal branches and collaterals with minimal side effects requiring no medical intervention. It helps increase the MDCT diagnostic accuracy and select appropriate treatment protocol.